Cultures lithiques dans les monts Mandara au Cameroun - Narcisse Santores Tchandeu (Afrique Archéologie Arts, 2009)
Research work carried out recently in the Mandara mountains in northern Cameroon enable us to appreciate the dynamism of its cultural stone heritage through the standing stones, rock art, mobile art and various stone structures. All these aspects give this cultural heritage a real social-historical, archaeological, anthropological, and even aesthetical interest, illustrated in diverse ritual practices, but also as an index of both social statutes and territorial markers.